1989
DOI: 10.1084/jem.170.4.1433
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid P component binds to cell nuclei in vitro and to in vivo deposits of extracellular chromatin in systemic lupus erythematosus.

Abstract: Serum amyloid P component (SAP) is the single plasma protein that, from the milieu of whole normal human serum, undergoes specific calcium-dependent binding to isolated DNA and chromatin in vitro. We now report for the first time that SAP in whole serum also undergoes calcium-dependent binding to nuclei of epidermal cells in sections of normal human skin and to nuclei of fixed Hep-2 cells, a human epithelial cell line. Furthermore, and most importantly, SAP was detected in association with unusual globular der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…In a recent report (45), Bickerstaff et al showed that in an otherwise healthy strain of mice, targeted deletion of the SAP gene led to the development of antinuclear autoimmunity and severe glomerulonephritis. Like CRP, SAP binds and can solubilize chromatin (46), and it binds to apoptotic and necrotic cells (47,48). Thus, the SLE-like phenotype of SAP-deficient mice was linked to their impaired handling and degradation of chromatin, which allowed for increased anti-DNA responses (45).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report (45), Bickerstaff et al showed that in an otherwise healthy strain of mice, targeted deletion of the SAP gene led to the development of antinuclear autoimmunity and severe glomerulonephritis. Like CRP, SAP binds and can solubilize chromatin (46), and it binds to apoptotic and necrotic cells (47,48). Thus, the SLE-like phenotype of SAP-deficient mice was linked to their impaired handling and degradation of chromatin, which allowed for increased anti-DNA responses (45).…”
Section: Discussionmentioning
confidence: 99%
“…Each subunit monomer has two Ca 2+ -binding sites and shows Ca 2+ -dependent binding to many different ligands, including certain oligosaccharides, glycosaminoglycans (Hamazaki 1987), fibronectin , C-reactive protein (Swanson et al, 1992), aggregated IgG (Brown and Anderson 1993), C1q (Sorensen et al, 1996), complement C4-binding protein (Sorensen et al, 1996), DNA (Pepys and Butler 1987), chromatin (Breathnach et al, 1989), histones (Hicks et al, 1992), and phosphoethanolamine-containing compounds such as phosphatidylethanolamine (Emsley et al, 1994). Interaction with these ligands localises SAP to elastic microfibrils , glomerular and alveolar basement membrane, arterioles, bronchioles, sarcolemma of cardiac and smooth muscle (Dyck et al, 1980), and all forms of amyloid .…”
Section: Serum Amyloid P Componentmentioning
confidence: 99%
“…In the presence of calcium ions, SAP can bind to several ligands such as amyloid fibrils of any type (4), agarose (8), heparin and dermatan sulfate (9), C1q (10,11), C4 binding protein (12,13), laminin (14), type V collagen (15), and phosphoethanolaminecontaining compounds such as phosphatidylethanolamine (16,17), DNA (18), chromatin (19,20), and histones (21,22).…”
Section: H Uman Serum Amyloid P Component (Sap)mentioning
confidence: 99%